PENGUATAN LITERASI DI FORUM KAJIAN ILMIAH PONDOK PESANTREN LIRBOYO KEDIRI - Moh. Turmudi; Reza Ahmad Zahid (Institut Agama Islam Tribakti Kediri, 2022)
The purpose of this service activity is to strengthen the scientific work of students who have standard standards and can be accounted for academically in accordance with the rules of the Indonesian language. The results of Islamic boarding school literacy assistance are directed at carrying out the mission of making pesantren a center for comprehensive and academically accountable scientific studies and publications of Islamic scholarship. Where this is realized by carrying out activities related to Islamic boarding school literacy on a massive and sustainable basis. As a first step for developing the role and function of Islamic boarding schools as centers of Islamic studies and able to adapt to the development of science and technology. FKI Pesantren Lirboyo Kediri is very representative to develop a literacy culture. Constructive collaboration with various parties will further strengthen the writing quality of the FKI team.